Modeling and PSO optimization of Humidifier-Dehumidifier desalination - Ahmadi, Mohammad Hossein; Afshar, Mohammad Ali; Naseri, Ali; Bidi, Mokhtar; Hadiyanto, H. (Center of Biomass & Renewable Energy, Diponegoro University, 2018)
The aim of this study is modeling a solar-air heater humidification-dehumidification unit with applying particle swarm optimization to find outÂ the maximum gained output ratio with respect to the mass flow rate of water and air entering humidifier, mass flow rate of cooling water entering dehumidifier, width and length of solar air heater and terminal temperature difference (TTD) of dehumidifier representing temperature difference of inlet cooling water and saturated air to dehumidifier as its decision variable. A sensitivity analysis, furthermore, is performed to distinguish the effect of operating parameters including mass flow rate and streamsâ€™ temperature. The results showed that the optimum productivity decreases by decreasing the ratio of mass flow rate of water entering humidifier to air ones.Article History: Received: July 12th 2017; Revised: December 15th 2017; Accepted: 2nd February 2018; Available onlineHow to Cite This Article: Afshar, M.A., Naseri, A., Bidi, M., Ahmadi, M.H. and Hadiyanto, H. (2018) Modeling and PSO Optimization of Humidifier-Dehumidifier Desalination. International Journal of Renewable Energy Development, 7(1),59-64.https://doi.org/10.14710/ijred.7.1.59-64